Differences in Unfolded Protein Response Pathway Activation in the Lenses of Three Types of Cataracts - Yang, Jing; Zhou, Sheng; Gu, Jianjun; Wang, Yujuan; Guo, Minfei; Liu, Yizhi (PloS one, 2015)
To investigate the activation of three unfolded protein response (UPR) pathways in the lenses of age-related, high myopia-related and congenital cataracts. Lens specimens were collected from patients during small incision cataract surgery. Lenses from young cadaver eyes were collected as normal controls. Real-time PCR and Western blotting were performed to detect the expression of GRP78, p-eIF2α, spliced XBP1, ATF6, ATF4 and p-IRE1α in the lenses of normal human subjects and patients with age-related, myopia-related or congenital cataracts. In the lenses of the age-related and high myopia-related cataract groups, the protein levels of ATF6, p-eIF2α and p-IRE1α and the gene expression levels of spliced XBP1, GRP78, ATF6 and ATF4 were greatly increased. Additionally, in the congenital cataract group, the protein levels of p-eIF2α and p-IRE1α and the gene expression levels of spliced XBP1, GRP78 and ATF4 were greatly increased. However, the protein and gene expression levels of ATF6 were not up-regulated in the congenital cataract group compared with the normal control group. The UPR is activated via different pathways in the lenses of age-related, high myopia-related and congenital cataracts. UPR activation via distinct pathways might play important roles in cataractogenesis mechanisms in different types of cataracts.